Gene network underlying the glial regenerative response to central nervous system injury. Issue 1 (25th September 2017) - Kato, Kentaro; Losada‐Perez, Maria; Hidalgo, Alicia
Abstract : Although the central nervous system does not regenerate, injury induces repair and regenerative responses in glial cells. In mammals, activated microglia clear up apoptotic cells and debris resulting from the injury, astrocytes form a scar that contains the lesion, and NG2‐glia elicit a prominent regenerative response. NG2‐glia regenerate themselves and differentiate into oligodendrocytes, which remyelinate axons leading to some recovery of locomotion. The regenerative response of glial cells is evolutionarily conserved across the animals and Drosophila genetics revealed an underlying gene network. This involves the genes Notch, kon‐tiki, eiger, dorsal, and prospero, homologues of mammalian Notch1, ng2, TNF, NFκB, and prox1, respectively. Feedback loops between these genes enable a surge in proliferation in response to injury and ensuing differentiation. Negative feedback sets a timer for proliferation, and prevents uncontrolled growth that could lead to glioma. Remarkable parallels are found in these genetic relationships between fruit flies and mammals. Drosophila findings provide insights into gene functions that could be manipulated in stem cells and progenitors for therapeutic repair. Developmental Dynamics 247:85–93, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: The glial regenerative response (GRR) to CNS injury is evolutionarily conserved across the animals. It involves the balanced regulation of neuropile glia proliferation and differentiation. Research using Drosophila genetics and mammalian findings has uncovered a gene network underlying this response. In Drosophila, altering these gene functions can shift the response of glia from prevention to promotion of repair, or glial tumoural over‐growth. The GRR gene network is homeostatic and provides structural robustness.